Respuesta :

Answer: X = y - yi - 7i

               Y = (x + 7i)/(1 - i)

Step-by-step explanation: for the case of (X) you only need to pass the 7i to the other side with the subtraction sign (-7i), then we get this equation:

x + 7i = y − yi

X = y - yi - 7i

in the case of the (Y), first we select the common multiple.

y - yi = y(1 - i)

if we replace it in the original expression, we get the following equation:

x + 7i = y(1 - i)

after that you can pass the value (1 - i) to the other side dividing,

Y = (x + 7i)/(1 - i)

Answer:

x=y-yi-7i

y=ix+x-7+7i

        2      

Step-by-step explanation: